Bridging knowledge gaps in fish health management through education, research, and biosecurity - Zornu, Jacob; Tavornpanich, Saraya; Shimaa, Ali E.; Addo, Samuel; Nyaga, Philip; Dverdal, Mona Jansen; Norheim, Kari; Brun, Edgar; Cudjoe, Kofitsyo S. (Frontiers in Sustainable Food Systems, 2023)
Education, research, and biosecurity have global recognition as strong pillars of sustainable aquaculture development. In many developing countries, insufficient knowledge and awareness among stakeholders regarding the relevance of education, research, and biosecurity have influenced aquaculture sustainability negatively. To uncover the gaps in education, research, and biosecurity practices in aquatic animal health management, we conducted a questionnaire-based study in various East and West African countries. By adopting the methodology of self-reporting data, we invited a significant number of individuals to participate in the study. In the end, 88 respondents contributed, with the majority from Ghana (47) and Kenya (20), and 21 respondents from five other East and West African nations. The results revealed substantial educational gaps, including the need for practical training in aquatic animal health management, nutrition, and genetics. Respondents also emphasized the importance of creating additional national aquaculture research institutions and augmented funding to enable them to address industry needs. Governments of the represented nations should actively intervene by providing the essential logistics and capacity to support aquaculture research and development. Informed government involvement is paramount for bridging the disconnection among all stakeholders, as revealed in the results. Furthermore, the lack of biosecurity measures and the understanding of the importance of biosecurity measures in the industry addressed through awareness creation. Creating awareness on biosecurity underpinned with national aquaculture biosecurity policies can prevent disease incidences in the industry. The outcomes of this study can serve as a vital working document to enhance aquatic animal health management in East and West Africa, thereby fostering sustainable and resilient aquaculture.